Personalized reconstruction of genital defects in complicated wounds with vertical rectus abdominis myocutaneous flaps including urethral neo-orifice - Horch, Raymund E.; Ludolph, Ingo; Arkudas, Andreas; Cai, Aijia (Journal of Personalized Medicine, 2021)
Non-healing extensive wounds in the perineal region can lead to severe soft tissue infections and disastrous complications, which are not manageable with conservative measures. Specifically in recurrent or advanced pelvic malignancies, irradiation often leads to extensive scarring and wound breakdown, resulting in significant soft tissue defects during surgical tumor excision. Among several surgical options to reconstruct the perineum, the transpelvic vertical rectus abdominis myocutaneous (VRAM) flap has proven to be one of the most reliable methods. Specific modifications of this flap allow an individualized procedure depending on the patient’s needs. We modified this technique to include the urethral orifice into the skin paddle of VRAM flaps in three patients as a novel option to circumvent urinary diversion and maintain an acceptable quality of life.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Neourethra; Perineal reconstruction; Urethral reconstruction; VRAM flap